The Effect of Knowledge Investment, Perceived Return and Risk and Technological Advances on Investment Interest of Medan City Students in the Capital Market - Salmah; Kartini Harahap (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the influence of knowledge investment, perceived return and risk and technological advances on investment interest of students Medan City in the capital market. The population in this study were active students from universities of Medan city who have currently investing in the capital market, either in the form of stocks or mutual funds. The sample in the research were 100 respondents. The research method used is quantitative method. Data collection techniques used questionnaires. The analysis technique used multiple linear regression analysis using SPSS. The results of this research shows that knowledge investment, perceived return and risk and technological advances have a positive and significant effect on investment interest of students Medan City in the capital market.